Peningkatan Kemampuan Pemecahan Masalah Matematis Melalui Etno Stem PjBL Berbasis Budaya Dayak - Niken Eka Priyani (Jurnal Didaktika Pendidikan Dasar, 2024)
The obstacle to learning Mathematics at state Elementary Schools 29 Idai is that students do not understand how to integrate the concepts learned at school with everyday life. This causes students' mathematical problem solving abilities to be very low. The aim of this research is to improve mathematical problem solving abilities through Etno STEM PjBL based on Dayak culture. The research method for this research is Classroom Action Research (PTK) with 2 cycles. The research subjects were all sixth grade students. The research instruments used were mathematical problem solving questions, observation sheets and documentation. Data analysis was carried out descriptively quantitatively. The results of the research show that there is an increase in problem-solving abilities through Dayak culture-based STEM PjBL learning in building materials. In this lesson, students learn mathematics and immediately apply it to life in the Dayak community by making various kinds of products such as traps (fishing tools), capan, and takin.